A CASE REPORT: EARLOBE RECONSTRUCTION ON CONGENITAL AURICULAR LOBE DEFECT USING Z-PLASTY - Amatullah, Nida' Fahima; Iswinarno Doso Saputro (Universitas Airlangga, 2024)
Highlights: Congenital ear defects typically result from growth failures during the fifth to ninth weeks of gestation or from mechanical stress during this period. Auricular lobuloplasty using the Z-plasty flap technique effectively addresses earlobe defects, resulting in optimal aesthetic outcomes with no keloid formation, minimal scarring, and no complications. Abstract: Introduction: Earlobe defects, often due to embryonal growth failure or injury, can affect aesthetics and social interactions despite not impacting hearing. Earlobe defect can be formed either from birth as congenital defect or secondary manifestation of other causes such as tumor and external factor such as earring usage or trauma. This study aimed to address these issues by performing auricular lobuloplasty using a Z-plasty flap technique. The procedure, crucial for protecting the auditory canal and facilitating eyeglass use, was successful in achieving the desired aesthetic outcome. Data on microtia prevalence, particularly in Indonesia, highlights the need for such reconstructive surgeries. Case Illustration: A 9-year-old boy underwent auricular lobuloplasty to correct a cleft earlobe deformity, which caused social discomfort. The surgery, performed under general anesthesia, utilized a Z-plasty technique to lengthen and reorient the scar. Postoperative care included wound dressing changes and oral pain medication. After two weeks, satisfactory results were observed with no reported complications. Discussion: The study on congenital ear deformities focuses on Z-plasty for earlobe reconstruction, detailing classifications, surgical techniques, and case results. The surgery was successful with minimal scarring and no keloid formation. Using Weerda's classification, the technique showed minimal scarring and no keloid formation. The approach, emphasizing proper skin envelope and alignment with Langer lines, offers effective aesthetic restoration, making it a valuable reference for future earlobe reconstruction cases. Conclusion: Utilizing Z-plasty for earlobe defect reconstruction aids in improving the earlobe's appearance with minimal to no complications.